Menopausal symptoms and their associations with disordered eating and physical activity behaviours - Immonen, Ella (2025)
The aim of this master’s thesis was to investigate the associations between menopausal symptoms and disordered eating behaviours, as well as the associations between menopausal symptoms and physical activity behaviours. This study utilised the data from the EsmiRs study conducted in the University of Jyväskylä. Previous research has revealed a surprisingly high prevalence of disordered eating among menopausal women. Consequently, menopause has been recognized as a high-risk period for the onset or recurrence of eating disorders. Despite this, the topic remains under-researched, highlighting the importance of further investigation into this population.